PENGGUNAAN METODE EULER PADA PERSAMAAN DIFERENSIAL ORDE DUA PADA RANGKAIAN LISTRIK SERI LC - MAIYENA, SRI (IAIN Batusangkar, 2011)
The use of analytical methods in solving some forms of differential equations, specifically the non-linear differential is difficult to conduct. The alternative is by using the numerical method. The numerical method used is the euler method which applies the second order differential equation on an LC series circuit. By using fortran program, the strong current and charge are obtained from t=0 and t=2.5 second.Key words: Differential Equation, LC series circuit, numerical method, euler method